Haemodynamic consequences of recurrent insulin‐induced hypoglycaemia. (January 2014) - Quadri, Syed; Prathipati, Priyanka; Jackson, Debra W; Jackson, Keith E
Summary Recurring insulin‐induced hypoglycaemia (RIIH) often occurs during the therapeutic management of insulin‐dependent diabetes mellitus. Controversy currently exists in the literature as to the ability of insulin and/or hypoglycaemia to promote hypertension. Could insulin and/or hypoglycaemia promote adverse pressor effects? If so, under what conditions and through what mechanism? Thus, the present study was performed to evaluate the hypothesis that RIIH produces hypertension via induction of heme oxygenase (HO)‐1, promoting a significant increase in endogenous carbon monoxide (CO). Male Sprague‐Dawley rats were treated for 2 weeks with varying doses of insulin (1, 3, 5, 7 and 9 U/kg, s.c.) or vehicle and fed normal rat chow or a zinc diet (1 mmol/L) for 2 weeks. Tail‐cuff blood pressure, food intake and blood glucose states were monitored daily. A dose‐dependent decrease in blood glucose was observed in insulin‐treated rats. Blood pressure was significantly elevated in rats treated with 9 and 7 U/kg insulin compared with those treated with other doses of insulin. However, there was no change in urine output among the groups. Feeding of a high‐zinc diet to rats treated with 7 U/kg insulin and treatment with the HO‐1 inhibitor zinc deuteroporphyrin 2, 4‐bis glycol (ZnDPBG; 20 mg/kg) after insulin injection resulted in a significant reduction in blood pressure compared with 7 U/kg insulin injection alone. In addition, HO‐1 protein levels in the heart and kidney and endogenous CO levels were reduced in 7 U/kg insulin‐treated rats fed the high‐zinc diet compared with those treated with the same dose of insulin alone. The results of the present study demonstrate that RIIH promotes hypertension and that restoration of normal CO levels with a high‐zinc diet and ZnDPBG reduces blood pressure.